Optimizing radiologist productivity and efficiency: Work smarter, not harder. Issue 155 (October 2022) - McGrath, Anika L.; Dodelzon, Katerina; Awan, Omer A.; Said, Nicholas; Bhargava, Puneet
Highlights: Incorporating personal productivity methodologies can enhance workplace productivity. Workstations can be optimized to automate repetitive tasks to improve efficiency. Institutions need to invest in informatics to maximize personal productivity. Delegate non-clinical tasks to staff to reduce administrative burdens on physicians. Artificial intelligence and smart report templates will further maximize productivity. Abstract: Radiologists' personal productivity and efficiency are critically important for both improving patient outcomes and protecting clinician well-being. There are several solutions that individuals can implement to improve personal productivity and efficiency in the radiology workroom. Strategies include understanding the psychology behind productivity, using personal productivity methodologies to accomplish daily tasks, and learning to modulate stress to optimize performance. Institutional infrastructure requirements include a robust departmental commitment to information technology and informatics, including universal log-in systems, internal websites, and dashboards. The workstation itself can be optimized by utilizing hanging protocols, customized keyboard shortcuts, hotkeys, advanced scripts, gaming mice, and other input devices. Personal devices like smartphones can be harnessed to maximize productivity by using online storage applications and radiology-specific applications to augment knowledge. Reading room layouts must be designed to minimize interruptions and workstations must consider ergonomics to prevent fatigue and strain. High-efficiency teams also need to be created to allow radiologists to delegate non-clinical tasks to reduce administrative burdens. Lastly, continued advances in artificial intelligence including the use of smart report templates will lead to substantial gains in radiologists' productivity and efficiency.